Intramuscular injection of prostaglandins with different trademarks in Balinese cattle (Bos sondaicus) on the speed and duration of estrus - Fadielah, Basri; Septian, I Gede Nano; Gifari, Zaid Al (Faculty of Agriculture, Tompotika Luwuk University, 2025)
The aim of this study was to compare the effectiveness of different brands of intramuscularly injected prostaglandin hormones on the speed and duration of estrus in Bali cattle. The study used 21 Bali cattle as subjects, divided into three treatment groups: P1 received 5 ml of Capriglandin, P2 received 5 ml of Lutalyse, and P3 received 2 ml of Juramate. The data collected included the speed and duration of estrus in hours. The results showed that for the speed of estrus onset, P1 required 69 hours, P2 56 hours, and P3 55 hours. Regarding the duration of estrus, P1 took 17 hours, P2 14 hours, and P3 13 hours. The findings indicate that the Juramate hormone resulted in the quickest onset of estrus, while the Capriglandin hormone led to a longer duration of estrus compared to the other hormones.